2004
DOI: 10.1007/s00424-003-1087-y
|View full text |Cite
|
Sign up to set email alerts
|

Organic anion transport is the primary function of the SLC17/type I phosphate transporter family

Abstract: Recently, molecular studies have determined that the SLC17/type I phosphate transporters, a family of proteins initially characterized as phosphate carriers, mediate the transport of organic anions. While their role in phosphate transport remains uncertain, it is now clear that the transport of organic anions facilitated by this family of proteins is involved in diverse processes ranging from the vesicular storage of the neurotransmitter glutamate to the degradation and metabolism of glycoproteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
134
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(135 citation statements)
references
References 48 publications
(97 reference statements)
1
134
0
Order By: Relevance
“…SLC17 is a type I phosphate transporter family consisting of eight genes that are classified into three distinct subfamilies: (i) SLC17A1-4 (NPT1, NPT3, NPT4, and Na ϩ /PO4 2Ϫ cotransporter homologue), Na ϩ and inorganic phosphate cotransporters, (ii) SLC17A5 (sialin), a lysosomal H ϩ /sialic acid cotransporter, and (iii) SLC17A6-8, VGLUT (5). We found that a fourth subfamily, tentatively designated SLC17A9, was identified in a genome data bank screening (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…SLC17 is a type I phosphate transporter family consisting of eight genes that are classified into three distinct subfamilies: (i) SLC17A1-4 (NPT1, NPT3, NPT4, and Na ϩ /PO4 2Ϫ cotransporter homologue), Na ϩ and inorganic phosphate cotransporters, (ii) SLC17A5 (sialin), a lysosomal H ϩ /sialic acid cotransporter, and (iii) SLC17A6-8, VGLUT (5). We found that a fourth subfamily, tentatively designated SLC17A9, was identified in a genome data bank screening (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In glutamatergic neurons, glutamate is loaded into synaptic vesicles before its release into the synaptic cleft. This essential process is carried out by the VGLUTs, and inactivation of VGLUTs ablates glutamate release and neurotransmission (10)(11)(12)(13)(14)(15). Three distinct VGLUTs have been described, and anatomical studies have established that VGLUT1, 2, and 3 are expressed by largely nonoverlapping and functionally distinct populations of glutamatergic neurons in the nervous system (16).…”
mentioning
confidence: 99%
“…Vesicular storage and subsequent exocytosis of L-glutamate is the major pathway for excitatory signal transmission in the central nervous system (1)(2)(3). Vesicular glutamate transporters (VGLUTs) 2 are essential for the vesicular storage of L-glutamate through active transport of L-glutamate into synaptic vesicles at the expense of ⌬H ϩ established by vacuolar H ϩ -ATPase (V-ATPase) (1).…”
mentioning
confidence: 99%
“…Vesicular glutamate transporters (VGLUTs) 2 are essential for the vesicular storage of L-glutamate through active transport of L-glutamate into synaptic vesicles at the expense of ⌬H ϩ established by vacuolar H ϩ -ATPase (V-ATPase) (1). There are three isoforms of VGLUT, denoted VGLUT1, VGLUT2, and VGLUT3 on the basis of the order of their discovery (2, 4 -6).…”
mentioning
confidence: 99%
See 1 more Smart Citation